2011
DOI: 10.1097/mao.0b013e31821ac88a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Electroacoustic Device Failure and Electroacoustic Reimplantation With Hearing Preservation

Abstract: Hearing can be preserved in EAS reimplantation using EAS surgical techniques. Air accumulation can be avoided or treated with a myringotomy tube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Thus, the preservation of low-frequency residual hearing is paramount to ensure ongoing auditory performance using EAS. Our data confirms that in EAS patients, residual low-frequency hearing can be preserved after reimplantation, which is in keeping with a recent and only report in the literature by Kamat et al (7). Other reimplantation outcomes in partial deafness patients in the (17), who described patients with partially preserved or compromised residual hearing after initial EAS surgery who were reimplanted with standard length electrodes and subsequently had no preservation of their residual hearing.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, the preservation of low-frequency residual hearing is paramount to ensure ongoing auditory performance using EAS. Our data confirms that in EAS patients, residual low-frequency hearing can be preserved after reimplantation, which is in keeping with a recent and only report in the literature by Kamat et al (7). Other reimplantation outcomes in partial deafness patients in the (17), who described patients with partially preserved or compromised residual hearing after initial EAS surgery who were reimplanted with standard length electrodes and subsequently had no preservation of their residual hearing.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, Kamat et al (7) reported on an adult patient with EAS who had evidence of complete hearing preservation after EAS reimplantation with a conventional Sonata Flex EAS electrode. Reimplantation poses a unique challenge in EAS patients as hearing preservation needs to be maintained to ensure superior auditory performance.…”
mentioning
confidence: 98%
“…Up to now, there exists 1 report on incomplete insertion of a Flex 24 array in a patient with HP above 60 dB up to 500 Hz before and 250 Hz after revision surgery (16). To our knowledge, we offer the first report on reimplantation in a group of patients with complete HP.…”
Section: Discussionmentioning
confidence: 89%
“…According to a literature review, most studies regarded the following situations as reimplantation: (1) removal of the initial electrodes for various reasons and implantation of a new device on the ipsilateral or contralateral side, which was the most common scenario defined as reimplantation ( Lassig et al, 2005 ); (2) replacement of the failed hybrid CI with short electroacoustic stimulation (EAS) electrodes or full-length electrodes ( Kamat et al, 2011 ; Jayawardena et al, 2012 ; Dunn et al, 2015 ); (3) reinsertion of the initial electrodes into the cochlea in cases of device migration ( Luo et al, 2020 ); (4) reinsertion of the initial electrodes into the cochlea on the operation day or within a few days of the operation due to the electrodes in incorrect insertion places, such as the internal auditory canal, eustachian tube, vestibul. ( Gözen et al, 2019 ); and (5) simultaneous implantation on both sides when patients with unilateral CI accept reimplantation surgery ( Tang et al, 2019 ).…”
Section: Part Ii: Current Deficiencies and Future Research Directionsmentioning
confidence: 99%